The use of High-Flow Nasal Oxygen Therapy in 4 dogs undergoing bronchoscopy - de Jaureguizar Tesas, Maria Rosa; Matson, Hannah; Tappin, Simon; Thomas, Emily (Frontiers in Veterinary Science, 2023)
Introduction: High-Flow Nasal Oxygen Therapy is a method to deliver warmed, humidified air-oxygen blended at high flow rates to patients through a nasal cannula using a specialized, commercially available machine. This is a well-tolerated, safe and effective method for oxygen delivery to healthy and hypoxemic dogs. Patients undergoing bronchoscopic procedures frequently develop hypoxemia. Human trials have shown a reduction in incidents of hypoxemic events and higher pulse oximeter oxygen saturation during bronchoscopies in patients on High-Flow Nasal Oxygen. Material and methods: This is a single-centre, prospective case series. All dogs weighing between 5 and 15kg and undergoing bronchoscopy during the study period (03/07/2022-01/10/2022) were eligible Standard statistical software was used to assess distribution and calculate mean or median values for baseline patient information, disposable material, monitoring data and complications recorded. Results: Twelve patients were eligible for the study of which four were enrolled. No complications related to the use of High-Flow Nasal Oxygen Therapy were recorded. Two of the patients were re-intubated post bronchoscopy due to clinician preference for recovery. One of the patients had a self-limiting period of hypoxemia with a pulse oximeter oxygen saturation of 84% for one minute during bronchoalveolar lavage, and whilst undergoing High-Flow Nasal Oxygen administration. Conclusion: All dogs tolerated the High-Flow Nasal Oxygen Therapy well with no complications recorded. This initial pilot data suggests that the use of High-Flow Nasal Oxygen therapy during bronchoscopy is safe and feasible, although it may not prevent hypoxemia in these patients. The use of High-Flow Nasal Oxygen Therapy during bronchoscopy in small patients carries multiple potential benefits and further studies to compare its efficacy against other traditional and other oxygen delivery systems are warranted in this patient population.